2007
DOI: 10.1021/np070007v
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Cytotoxic Cyclotides:  Cycloviolacin O2 Disrupts Lipid Membranes

Abstract: In recent years, the cyclotides have emerged as the largest family of naturally cyclized proteins. Cyclotides display potent cytotoxic activity that varies with the structure of the proteins, and combined with their unique structure, they represent novel cytotoxic agents. However, their mechanism of action is yet unknown. In this work we show that disruption of cell membranes plays a crucial role in the cytotoxic effect of the cyclotide cycloviolacin O2 (1), which has been isolated from Viola odorata. Cell via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
119
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 40 publications
4
119
1
Order By: Relevance
“…We (29) have also shown that some cyclotides assemble into tetramers and octamers in solution and thus potentially could assemble into pores in membranes. Further evidence for their ability to disrupt membranes is seen from their hemolytic activity (30) and their cytotoxic effect on a human lymphoma cell line (31).…”
Section: Discussionmentioning
confidence: 99%
“…We (29) have also shown that some cyclotides assemble into tetramers and octamers in solution and thus potentially could assemble into pores in membranes. Further evidence for their ability to disrupt membranes is seen from their hemolytic activity (30) and their cytotoxic effect on a human lymphoma cell line (31).…”
Section: Discussionmentioning
confidence: 99%
“…Bioassays show that cyclotides belonging to both Möbius and bracelet subfamilies have cytotoxic (9) and hemolytic (19) properties. Studies with model membranes show that kalata B1 (kB1) 6 (20,21), the prototypic Möbius cyclotide, and cycloviolacin O 2 (cyO2) (22), the prototypic bracelet cyclotide, can bind and disrupt lipid bilayers. In addition, the majority of cyclotides have a surface-exposed patch of hydrophobic residues that has been suggested to be required for their bioactivities (23,24).…”
mentioning
confidence: 99%
“…Cyclotides express a diversity of peptide sequences within their backbone loops and have a broad range of biological activities, including uterotonic (2), anti-HIV (3), antimicrobial (4), and anticancer activities (5). Accordingly, they are of great interest for pharmaceutical applications.…”
mentioning
confidence: 99%